2002
DOI: 10.1161/01.cir.0000015697.59592.07
|View full text |Cite
|
Sign up to set email alerts
|

No-Reflow Phenomenon and Lesion Morphology in Patients With Acute Myocardial Infarction

Abstract: Background-The no-reflow phenomenon is associated with poor functional and clinical outcomes for patients with acute myocardial infarction (AMI). In the era of primary intervention, accurately identifying lesions at high risk of no reflow is of crucial importance. At present, no study into the relationship between lesion morphology and no reflow has been performed. The aim of this study was to investigate the relationship between preintervention intravascular ultrasound (IVUS) lesion morphology and the no-refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
156
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(179 citation statements)
references
References 29 publications
(21 reference statements)
12
156
1
2
Order By: Relevance
“…However, it was reported that reperfusion therapy resulted in insufficient coronary microcirculation attributable to reperfusion injury, such as oxygen-free radical injury, 28,29 calcium overload, microvascular spasm, 10 neutrophil plugging of the microvessels, 30 and tissue edema 8 or embolization of the coronary microvasculature attributable to dissemination of thrombi and the contents of the disintegrated atheroma in the lesion to distal parts of the coronary vasculature. 31,32 In the present study, in 75% of the patients with severe microvascular injury, an ST-segment reelevation was observed in the absence of epicardial mechanical obstruction immediately after PCI. Therefore, microvascular injury is not only determined by the size of the infarction associated with myocardial ischemia but also by reperfusion injury and interventioninduced release of the thrombi and the contents of the disintegrated atheroma.…”
Section: Microvascular Injury and Coronary Flow Velocity Patternsupporting
confidence: 49%
“…However, it was reported that reperfusion therapy resulted in insufficient coronary microcirculation attributable to reperfusion injury, such as oxygen-free radical injury, 28,29 calcium overload, microvascular spasm, 10 neutrophil plugging of the microvessels, 30 and tissue edema 8 or embolization of the coronary microvasculature attributable to dissemination of thrombi and the contents of the disintegrated atheroma in the lesion to distal parts of the coronary vasculature. 31,32 In the present study, in 75% of the patients with severe microvascular injury, an ST-segment reelevation was observed in the absence of epicardial mechanical obstruction immediately after PCI. Therefore, microvascular injury is not only determined by the size of the infarction associated with myocardial ischemia but also by reperfusion injury and interventioninduced release of the thrombi and the contents of the disintegrated atheroma.…”
Section: Microvascular Injury and Coronary Flow Velocity Patternsupporting
confidence: 49%
“…Impact of thrombus burden on myocardial reperfusion: In the present study, we found that an RLD of the IRA ≥ 3.5 mm and a lesion length ≥ 3.5 mm were the independent predictors of unsuccessful reperfusion. Our finding was consistent with recent studies 22,23) which demonstrated that large vessels usually contain large amounts of plaque burden and high-burden thrombus formation. Furthermore, our clinical observations led us understand that the longer the lesion length, the greater the plaque burden.…”
Section: Discussionsupporting
confidence: 94%
“…During coronary intervention, the thrombus is crushed and the plaque is artificially ruptured, which in turn, cause a release of macro-and microthrombus, and lipid pool-like contents. 22,23) These materials subsequently cause macro-and microembolism, and microvascular dysfunction. 22,23) The dislodged thrombi further activate more platelets and therefore, the thrombosis cascade, and this ultimately yields slow-flow or no-reflow in the IRA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, microvascular injury is determined not only by the size of the infarct but also by reperfusion injury, 16 PTCA-induced thrombus, and atheroma fragmentation. 17 Indeed, patients with severe microvascular injury immediately after PTCA have a higher frequency of ST-segment re-elevation 11 or incomplete ST-segment resolution, 18 and a continuously declining post-PTCA velocity has been linked to vessel reocclusion. 19 Several studies have shown that patients with no reflow on myocardial contrast echocardiography 20 or Doppler guidewire assessment 9,11,12 have poor functional LV recovery and a high frequency of complications such as CHF, pericardial effusion, cardiac tamponade, and cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%